Penerapan Fungsi Manajemen Keuangan Pada Perusahaan CV. Canbe Kosmetik Indonesia - Ahmad Fauzi (Universitas Maritim AMNI Semarang, 2024)
Financial management as an integral part of general management has a crucial role in the survival and growth of a company. In a constantly changing business environment with complex market dynamics, the application of financial management functions is becoming increasingly crucial in determining the direction and financial performance of the company. In this study, the approach used is a qualitative approach, which is a research process and understanding based on methodologies that investigate social phenomena and human problems. This research has a characteristic that lies in its purpose, namely describing, studying and explaining the phenomenon to be studied. Which contains the results of research on CV. Canbe Kosmetik Indonesia, the application of the financial management function is running well as the SOP set by the company. By applying the functions of financial management itself in the form of planning, organizing, directing, coordinating, and supervising.